2019
DOI: 10.2174/1871520618666180731093433
|View full text |Cite
|
Sign up to set email alerts
|

Gedunin, A Neem Limonoid in Combination with Epalrestat Inhibits Cancer Hallmarks by Attenuating Aldose Reductase-Driven Oncogenic Signaling in SCC131 Oral Cancer Cells

Abstract: Background and Objectives: Aldose Reductase (AR), a polyol pathway enzyme that mediates diabetic complications is implicated in tumour development and progression. This study was undertaken to determine whether gedunin, a neem limonoid prevents the hallmarks of cancer by inhibiting AR and the associated downstream PI3K/Akt/mTOR/ERK/NF-κB signalling axis in the SCC131 oral cancer cell line. Methods: The expression of AR and key molecules involved in cell proliferation, apoptosis, autophagy, invasion and angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…This results in the AKT/mTOR-mediated regulation of angiogenesis, EMT, migration and invasion at the same time, subsequently causing metastasis. In a particular study, a neem limonoid, gedunin, in association with epalrestat, an aldose reductase inhibitor used for the treatment of diabetic neuropathy, was found to inhibit cell migration by inhibiting AKT/mTOR signaling in squamous cell carcinoma (SCC)-131 cells [122]. In another study, C-reactive protein (CRP) increased the invasion and migration of OSCC cells plausibly via the activation of the AKT/mTOR axis [123].…”
Section: Invasion and Metastasismentioning
confidence: 99%
“…This results in the AKT/mTOR-mediated regulation of angiogenesis, EMT, migration and invasion at the same time, subsequently causing metastasis. In a particular study, a neem limonoid, gedunin, in association with epalrestat, an aldose reductase inhibitor used for the treatment of diabetic neuropathy, was found to inhibit cell migration by inhibiting AKT/mTOR signaling in squamous cell carcinoma (SCC)-131 cells [122]. In another study, C-reactive protein (CRP) increased the invasion and migration of OSCC cells plausibly via the activation of the AKT/mTOR axis [123].…”
Section: Invasion and Metastasismentioning
confidence: 99%
“…The overexpression and the increased activity of aldose reductase enzymes in different human cancers were also reported [66]. Aldose reductase enzymes were found to be involved in the tumorigenesis process via the production of growth factors that promote cell proliferation and inflammatory cytokines [17,18,67], thus aldose reductase activity inhibition could be evidence for cytotoxic effects. Aldose reductase inhibitors were found to be doxorubicin sensitivity enhancers as reported in the case of colon cancer cells and this can explain the synergistic effect on the cytotoxic activity with doxorubicin.…”
Section: Molecular Docking Studymentioning
confidence: 95%
“…The role of inhibition of aldose reductase in cancer management was investigated and proven through inhibition of aldose reductase-mediated ROS signaling and preventing activation of various oncogenic kinases and transcription factors that are responsible for the production of several carcinogenic mediators [ 17 , 18 ]. The use of doxorubicin, a potent chemotherapeutic drug against cancers, became limited due to its cardiotoxic effects [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gedunin's effect on oral cancer has been recently studied in vitro [35] and in vivo [34]. The in vivo approach investigated the effects of gedunin on the phosphoinositide 3-kinases (PI3K)/Akt/mammalian target of rapamycin (mTOR) and nuclear factor kappa B (NF-κB) signaling pathways, as well as hypoxia-inducible factor 1α (HIF1α)-mediated vascular endothelial growth factor (VEGF) signaling in a hamster buccal pouch (HBP) carcinogenesis model.…”
Section: Gastrointestinal Tract and Associated Cancersmentioning
confidence: 99%
“…The in vitro approach used the SCC131 oral cancer cell line to investigate how gedunin, alone or combined with epalrestat, prevented the hallmarks of cancer by inhibiting ARase and the associated downstream PI3K/Akt/mTOR/ERK/NF-κB signaling axis. Tanagala et al [35] concluded that gedunin, alone and combined, blocked cell proliferation, invasion, and angiogenesis, and induced cell death by blocking ARase-driven oncogenic signalling networks. Furthermore, gedunin combined with epalrestat was more effective than each single agent, suppressing the growth of SCC131 cells at half the concentrations used individually (0 to 180 µM for gedunin and 0 to 1.6 µM for epalrestat) [35].…”
Section: Gastrointestinal Tract and Associated Cancersmentioning
confidence: 99%